Programas de intervenção neuropsicológica precoce-preventiva : estimulação das funções executivas em escolares - Cardoso, Caroline de Oliveira (2017)
There is relative consensus that low level and quality of education are limiting factors of a country’s growth. Statistics show that many students have difficulties in learning or do not display the necessary abilities to succeed academically. Trying to reduce such difficulties, neuropsychology has developed remediation and rehabilitation interventions. There is, however, a need to invest in intervention programs that promote cognitive health and stimulate neurocognitive skills among children. These programs may potentiate cognitive processes and lead to short and long term benefits. Evidence shows that the executive functions (EF) have a crucial role in education, and are relevant in learning and in autoregulatory behavior. Given this context, the objective of this thesis was to develop and verify the effectiveness of an early and preventive neuropsychological intervention program with the intent of stimulating the EF among Elementary School students. The program was called Program of Neuropsychological Stimulation of Cognition in Students: emphasis on Executive Functions, or PENcE (an acronym from its original name in Portuguese, Programa de Estimulação Neuropsicológica da Cognição em Escolares: ênfase nas Funções Executivas). The First Study performed a systematic review of empirical studies about neuropsychological interventions of EF among children with typical development, looking for an overview that could guide the construction of the PENcE. Nineteen studies were found through the PRISMA method: most of them provided evidences that the children who participated in the intervention programs improved their executive functions. For the most part, they used computerized cognitive training to stimulate working memory. Other studies proposed a curricular approach to potentiate autoregulation. It was possible to observe that the studies are very heterogenic in terms of approach, methods, and closing measurement tools. Computerized trainings seem improve trained cognitive skills, but are limited in terms of transferring gains. Curricular programs seem more generalizable, with effects on transferring gains and functionality. The objective of the Second Study was to present the process of construction and content validity evidences for the PENcE. There were four steps involved in reaching that goal: internal stage of program organization; program construction; analysis by expert judges; and data integration and program finalization. All stages were important and contributed to improve the program. Furthermore, the assessment of the program (global and of each module) presented a level of agreement among judges equal to one, allowing for the achievement of content validity evidences. Finally, the Third Study investigated the effectiveness of the PENcE among children attending 3rd and 4th grades of Elementary School. It also analyzed the effects of transferring to other skills (executive, cognitive, academic, behavioral) beyond the main executive closings. From an initial sample of 160 children, 113 participated in the study. They were divided into two groups: experimental group (EG) (n=64) and control group (CG) (n=49). There were no differences between the groups before the intervention. After the study, the groups were compared, and the EG presented significant gains in inhibitory control, working memory, and abstract planning. There were transferring effects to other cognitive abilities (such as attention and fluid thinking), academic abilities (math and written skills), and changes in behavior (relationship and behavioral problems), and the overcame the CG. As a group, the findings from the three studies offer an early and preventive intervention program that has theoretical basis, has followed a rigorous construction process, and possesses content validity and effectiveness analysis. For future studies, it is suggested to extend and adapt the program to other age groups and to children who already present executive deficits, including learning difficulties and ADHD. Moreover, with the goal of contributing to public policies, it is recommended that the PENcE be implemented in public schools in developing countries, helping to bridge the gap between neuropsychology and education in a practical way.